Perbedaan Pengetahuan Ibu Balita Usia 6-24 Bulan Sebelum Dan Sesudah Diberikan Penyuluhan MP-ASI Dengan Menggunakan Media Poster Di Posyandu Kenanga V Kelurahan Semanggi Surakarta - Romdom, Muhammad Rohmat, Dwi Sarbini, SST, M.Kes, Nur Lathifah Mardiyati, S.Gz., MS (2016)
Background: The factor that influence the giving of MPASI is mother toddler's knowledge. The first research has been shown that the mother toddler's knowledge is less than 45%. One of the method that possible to do is counseling. Breastfeeding supplementary food counseling in Posyandu requires media to deliver information to the mothers easily. Posters selected as media outreach because it is able to spread information in a short time so it hopes that after attending counseling using posters can improve mother's knowledge in Posyandu Kenanga V in Semanggi Village Surakarta Objective: To know the differences of mother's knowledge of children ages 6-24 months before and after given breastfeeding supplementary food counseling by using poster as the media in Posyandu Kenanga V in Semanggi Village Surakarta. Methods: This study is a quantitative research and type of research is a quasi-experimental study. Data knowledge breastfeeding supplementary food mother using a questionnaire.Mother answered the question that has been available on the requestionnaire by herself. Results: The level of mother's knowledge before being given counseling more than half (54,3%) included to enough, meanwhile mother toddler's knowledge level after counseling has been good on more than half respondents (58,7%), based on the result of paired samples t test data show that the p-value 0,001 < 0,005. Conclusion: There was significant difference level knowledge before and after giving MP-ASI counseling. Research Suggestion: Mother should search some resources of giving MP-ASI so it can be improved the mother's knowledge about it.